Accurate EH Modelling and Achievable Information Rate for SLIPT Systems with Multi-Junction Photovoltaic Receivers - Shanin, Nikita; Ajam, Hedieh; Papanikolaou, Vasileios; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2024)
In this paper, we study simultaneous lightwave information and power transfer (SLIPT) systems employing photovoltaic optical receivers (RXs). We consider the case, where the optical RX is illuminated by ambient light and an intensity-modulated information-carrying free space optical (FSO) signal. To overcome the possible absence of ambient light, e.g., indoors or at night, we additionally assume that the optical RX receives a dedicated energy-bearing broadband optical signal. Additionally, to efficiently harvest energy from broadband light, we propose a novel optical RX based on multi-junction photovoltaic cells. Exploiting the analysis of the equivalent two-diode electrical circuit for the multi-junction photovoltaic RX, we carefully model the current flow through the photovoltaic cell and derive an accurate energy harvesting (EH) model. Furthermore, we also derive novel approximate EH models for the two cases, where the optical RX is equipped with a single and multiple p-n junctions, respectively. Next, we derive the distribution of the transmit information signal that maximizes the achievable information rate and, for a practical pulse amplitude modulated information signal, we determine the symbol error rate at the RX. We validate the proposed EH models by circuit simulations and show that the photovoltaic RXs saturate for high received signal powers. For single-junction RXs, we compare the proposed EH model with two well-known baseline EH models, which are based on maximum point tracking and a single-diode electrical circuit, respectively. We demonstrate that, in contrast to the proposed EH model, both baseline EH models are not able to fully capture the non-linear behavior of photovoltaic RXs. Moreover, our results reveal that, since multi-junction RXs allow a more efficient allocation of the optical power, they are more robust against saturation, and thus, are able to harvest significantly more power and achieve higher data rates than RXs employing a single p-n junction. Finally, we highlight a tradeoff between the information rate and harvested power in SLIPT systems and demonstrate that the proposed transmit signal distribution yields significantly higher achievable information rates compared to uniformly distributed transmit signals, which are optimal for linear optical information RXs.
CRIS-Team Scopus Importer:2024-07-19
Keywords: non-linear energy harvesting; optical receiver design; optical wireless communication; photovoltaics; SLIPT

Approximate Partially Decentralized Linear EZF Precoding for Massive MU-MIMO Systems - Kaziu, Brikena; Shanin, Nikita; Spano, Danilo; Wang, Li; Gerstacker, Wolfgang; Schober, Robert (100th Vehicular Technology Conference (VTC2024-Fall), 2024)

Average Harvested Power in THz WPT Systems Employing Resonant-Tunnelling Diodes - Shanin, Nikita; Clochiatti, Simone; Mayer, Kenneth; Cottatellucci, Laura; Weimann, Nils; Schober, Robert (2023 6th International Workshop on Mobile Terahertz Systems, IWMTS 2023, 2023)
In this paper, we study terahertz (THz) wireless power transfer (WPT) systems, where a single-antenna transmitter sends an energy signal to a single-antenna receiver. Since Schottky diodes, which are utilized in GHz energy harvesting (EH) circuits, are not usable for THz EH, we adopt an EH circuit employing a resonant tunnelling diode (RTD) at the receiver. However, the electrical properties of Schottky diodes and RTDs are different, and unlike EH receivers based on a single Schottky diode, an accurate EH model for RTD-based EH receivers is not available. Therefore, we model the dependency between the instantaneous harvested power at the EH device and the instantaneous received power by a piecewise non-linear function, whose parameters are adjusted to fit circuit simulation data. We formulate an optimization problem for the maximization of the average power harvested at the EH receiver subject to constraints imposed on the average and peak transmit powers. Then, for the solution of the formulated problem, we propose an equivalent monotonic EH model and we show that the optimal transmit signal distribution for WPT employs at most two mass points, which can be obtained as the solution of a min-max optimization problem. Our simulation results reveal that RTDs with low leakage currents and high breakdown voltages are preferable for WPT when the received signal power is low and high, respectively. Furthermore, we demonstrate that the proposed optimal input distribution yields significantly higher average harvested powers compared to a baseline scheme employing Gaussian transmit signals.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Schottky diodes; Simulation; Circuit simulation; RLC circuits; Receivers; Wireless power transfer; Resonant tunneling devices

A Wireless Joint Communication and Localization EMG-Sensing Concept for Movement Disorder Assessment - Brückner, Stefan; Weber, Jasmin; Michler, Fabian; Shanin, Nikita; Schober, Robert; Hagelauer, Amelie; Weigel, Robert; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Vossiek, Martin (IEEE Journal of Electromagnetics, RF and Microwaves in Medicine and Biology, 2023)
Real-time sensory recording of the musculoskeletal system function is an important tool for the diagnosis, treatment planning, and optimal treatment execution of diseases, such as Parkinson's disease and osteoarthritis. This article presents a new wireless joint communication and localization electromyography (EMG)-sensing concept. An on-body sensor beacon measures EMG signals and wirelessly transmits them. At the same time, the spatial position and movement of the beacon is determined with high precision in real time using these transmitted radio signals. The seamless integration of multiple sensors avoids the need to synchronize and individually set up multiple independently operating sensors. An outstanding feature of the radio localization approach is that it does not require proprietary ultra-wideband signals or complicated time synchronization protocols, allowing for small and energy-efficient implementation. To demonstrate this novel concept, a wireless 3D-localizable EMG sensor was developed and experimentally evaluated. This new type of sensing concept allows, for the first time, the time-synchronous measurement of muscle activity and the underlying movement of the associated body part. URL: https://ieeexplore.ieee.org/stamp/stamp.jsp?tp=&arnumber=10286030&isnumber=8000303<br
Keywords: Array signal processing; EMG; localization; radar tracking; radio communication

Dual-Task Supervised Learning for Distributed Spectrum Monitoring Applications - Shatov, Victor; Shanin, Nikita; Veihelmann, Christian Tobias; Perner, Bastian; Franchi, Norman; Lübke, Maximilian (EuCNC & 6G Summit, 2025)

EH Modelling and Achievable Rate for FSO SWIPT Systems with Non-linear Photovoltaic Receivers - Shanin, Nikita; Ajam, Hedieh; Papanikolaou, Vasileios; Schmauß, Bernhard; Cottatellucci, Laura; Schober, Robert (Proceedings - IEEE Global Communications Conference, GLOBECOM, 2023)
In this paper, we study optical simultaneous wireless information and power transfer (SWIPT) systems, where a photovoltaic optical receiver (RX) is illuminated by ambient light and an intensity-modulated free space optical (FSO) signal. To facilitate simultaneous information reception and energy harvesting (EH) at the RX, the received optical signal is first converted to an electrical signal, and then, its alternating current (AC) and direct current (DC) components are separated and utilized for information decoding and EH, respectively. By accurately analysing the equivalent electrical circuit of the photovoltaic RX, we model the current flow through the photovoltaic p-n junction in both the low and high input power regimes using a two-diode model of the p-n junction and we derive a closed-form non-linear EH model that characterizes the harvested power at the RX. Furthermore, taking into account the non-linear behaviour of the photovoltaic RX on information reception, we derive the optimal distribution of the transmit information signal that maximizes the achievable information rate. The proposed EH model is validated by circuit simulation results. Furthermore, we compare with two baseline models based on maximum power point (MPP) tracking at the RX and a single-diode p-n junction model, respectively, and demonstrate that in contrast to the proposed EH model, they are not able to fully capture the non-linearity of photovoltaic optical RXs. Finally, our numerical results highlight that the proposed optimal distribution of the transmit signal yields significantly higher achievable information rates compared to uniformly distributed transmit signals, which are optimal for linear optical information RX
CRIS-Team Scopus Importer:2024-12-16

EH Modelling and Achievable Rate for FSO SWIPT Systems with Non-Linear Photovoltaic Receivers - Shanin, Nikita; Ajam, Hedieh; Papanikolaou, Vasilis K.; Schmauß, Bernhard; Cottatellucci, Laura; Schober, Robert (Proceedings - IEEE Global Communications Conference, GLOBECOM, 2023)
In this paper, we study optical simultaneous wireless information and power transfer (SWIPT) systems, where a photo-voltaic optical receiver (RX) is illuminated by ambient light and an intensity-modulated free space optical (FSO) signal. To facilitate simultaneous information reception and energy harvesting (EH) at the RX, the received optical signal is first converted to an electrical signal, and then, its alternating current (AC) and direct current (DC) components are separated and utilized for information decoding and EH, respectively. By accurately analysing the equivalent electrical circuit of the photovoltaic RX, we model the current flow through the photovoltaic p-n junction in both the low and high input power regimes using a two-diode model of the p-n junction and we derive a closed-form non-linear EH model that characterizes the harvested power at the RX. Furthermore, taking into account the non-linear behaviour of the photovoltaic RX on information reception, we derive the optimal distribution of the transmit information signal that maximizes the achievable information rate. The proposed EH model is validated by circuit simulation results. Furthermore, we compare with two baseline models based on maximum power point (MPP) tracking at the RX and a single-diode p-n junction model, respectively, and demonstrate that in contrast to the proposed EH model, they are not able to fully capture the non-linearity of photovoltaic optical RXs. Finally, our numerical results highlight that the proposed optimal distribution of the transmit signal yields significantly higher achievable information rates compared to uniformly distributed transmit signals, which are optimal for linear optical information RXs.
CRIS-Team Scopus Importer:2024-12-16

Information Rate-Harvested Power Tradeoff in THz SWIPT Systems Employing Resonant Tunnelling Diode-based EH Circuits - Shanin, Nikita; Clochiatti, Simone; Mayer, Kenneth; Cottatellucci, Laura; Weimann, Nils; Schober, Robert (IEEE Transactions on Communications, 2024)
In this paper, we study terahertz (THz) simultaneous wireless information and power transfer (SWIPT) systems. Since coherent information detection is challenging at THz frequencies and Schottky diodes may not be efficient for THz energy harvesting (EH), we propose a novel THz SWIPT system design that employs unipolar amplitude shift keying (ASK) modulation at the transmitter (TX) and a resonant-tunnelling diode (RTD)-based EH circuit at the receiver (RX) to extract both information and power from the received signal. Furthermore, we propose a novel model for the dependence of the instantaneous output power of the RTD-based RX on the instantaneous received power, which is based on a non-linear and non-monotonic piecewise function, whose parameters are adjusted to fit circuit simulation results. To determine the information rate-harvested power tradeoff of the considered THz SWIPT system, we derive the distribution of the transmit signal that maximizes the mutual information between the transmit and received signals subject to constraints on the required average harvested power at the RX and the peak signal amplitude at the TX. Since the computational complexity needed for maximization of the mutual information may be infeasible for real-time THz SWIPT systems, we derive low-complexity suboptimal input signal distributions that maximize an achievable information rate numerically and in closed form for high and low required average harvested powers, respectively. Furthermore, based on the obtained results, we propose a suboptimal closed-form distribution of the transmit signal which can also guarantee a desired harvested power at the RX. Our simulation results show that while the proposed EH model can capture the non-monotonicity of RTD-based EH circuits in the THz band, baseline linear and non-linear EH models, developed for Schottky-diode-based EH circuits, can not. Furthermore, we demonstrate that a lower reverse current flow and a higher breakdown voltage of the employed RTD are preferable when the input signal power at the RX is low and high, respectively. We also show that all proposed input distributions yield practically identical SWIPT system performance. Moreover, we reveal that the information rate-harvested power tradeoff of THz SWIPT systems is determined by the peak amplitude of the TX signal and the maximum instantaneous harvested power for low and high received signal powers, respectively. Finally, we compare the proposed THz SWIPT system with two baseline schemes and confirm that the RX circuit parameters, mathematical EH models, and optimal transmit signal distributions have to be carefully designed to achieve high performance in THz SWIPT systems.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Amplitude shift keying; Circuits; Integrated circuit modeling; Internet of Things; non-linear energy harvesting; Resonant tunneling devices; resonant tunnelling devices; Schottky diodes; signal design; Terahertz communications; Terahertz communications

Joint Transmit Signal and Beamforming Design for Integrated Sensing and Power Transfer Systems - Mayer, Kenneth; Shanin, Nikita; You, Zhenlong; Lotter, Sebastian; Brückner, Stefan; Vossiek, Martin; Cottatellucci, Laura; Schober, Robert (IEEE International Conference on Communications, ICC 2024, 2024)
Integrating different functionalities, conventionally implemented as dedicated systems, into a single platform allows utilising the available resources more efficiently. We consider an integrated sensing and power transfer (ISAPT) system and propose the joint optimisation of the rectangular pulse-shaped transmit signal and the beamforming vector to combine sensing and wireless power transfer (WPT) functionalities efficiently. In contrast to prior works, we adopt an accurate non-linear circuit-based energy harvesting (EH) model. We formulate and solve a non-convex optimisation problem for a general number of EH receivers to maximise a weighted sum of the average harvested powers at the EH receivers while ensuring the received echo signal reflected by a sensing target (ST) has sufficient power for estimating the range to the ST with a prescribed accuracy within the considered coverage region. The average harvested power is shown to monotonically increase with the pulse duration when the average transmit power budget is sufficiently large. We discuss the trade-off between sensing performance and power transfer for the considered ISAPT system. The proposed approach significantly outperforms a heuristic baseline scheme based on a linear EH model, which linearly combines energy beamforming with the beamsteering vector in the direction to the ST as its transmit strategy.<br

LSTM-DNN-Based Joint Wireless Signal Waveform Classification and Blind Transmitter Localization - Shatov, Victor; Shanin, Nikita; Perner, Bastian; Su, Yanpeng; Franchi, Norman; Lübke, Maximilian (International Symposium on Wireless Communication Systems (ISWCS), 2024)

Markov Decision Process Based Design of SWIPT Systems: Non-Linear EH Circuits, Memory, and Impedance Mismatch - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2021)
In this paper, we study simultaneous wireless information and power transfer (SWIPT) systems employing practical non-linear energy harvester (EH) circuits. Since the voltage across the reactive elements of realistic EH circuits cannot drop or rise instantaneously, EHs have memory which we model with a Markov decision process (MDP). Moreover, since an analytical model that accurately models all non-linear effects and the unavoidable impedance mismatch of EHs is not tractable, we propose a learning based model for the EH circuit. We optimize the input signal distribution for maximization of the harvested power under a constraint on the minimum mutual information between transmitter (TX) and information receiver (IR). We distinguish the cases where the MDP state is known and not known at TX and IR. When the MDP state is known, the formulated optimization problem for the harvested power is convex. In contrast, if TX and IR do not know the MDP state, the resulting optimization problem is non-convex and solved via alternating optimization, which is shown to yield a limit point of the problem. Our simulation results reveal that the rate-power region of the considered SWIPT system depends on the symbol duration, the EH input power level, the EH impedance mismatch, and the type of EH circuit. In particular, a shorter symbol duration enables higher bit rates at the expense of a significant decrease in the average harvested power. Furthermore, whereas half-wave rectifiers outperform full-wave rectifiers in the low and medium input power regimes, full-wave rectifiers are preferable if the input power at the EH is high.
CRIS-Team Scopus Importer:2021-03-05
Keywords: energy harvesting; impedance matching; low-pass filters (LPF); Markov processes; non-linear circuits; rectennas; rectifiers; signal design; Wireless power transmission

Optimal Energy Signal Design for Multi-user MISO WPCNs with Non-linear Energy Harvesting Circuits - Shanin, Nikita; Hagelauer, Amelie; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2023)
The optimal energy signal design for wireless powered communication networks (WPCNs) enabling energy-sustainable communication for a large number of low-power devices is still an open problem in practical systems. In this work, we study a multi-user WPCN, where a multi-antenna base station (BS) sends an energy signal to multiple single-antenna users, which, in turn, harvest energy from the received signal and utilize it for information transmission in the uplink. In contrast to the existing works on multiple-input single-output (MISO) WPCN design, in this paper, we jointly optimize the energy signal waveform and downlink beamforming at the BS for energy harvesting (EH) devices described by non-linear circuit-based models. To this end, we assume that the BS broadcasts a pulse-modulated signal employing multiple energy signal vectors and we formulate an optimization problem for the joint design of the downlink transmit energy signal vectors, their number, the durations of the transmit pulses, and the time allocation policy for minimization of the average transmit power at the BS. We show that for single-user WPCNs, a single energy signal vector, which is collinear with the maximum ratio transmission (MRT) vector and drives the EH circuit at the user device into saturation, is optimal. Next, for the general multi-user case, we show that the optimal signal design requires a maximum number of energy signal vectors that exceeds the number of users by one and propose an algorithm to obtain the optimal energy signal vectors. Since the complexity of the optimal design is high, we also propose two suboptimal schemes for WPCN design. First, for asymptotic massive WPCNs, where the ratio of the number of users to the number of BS antennas, i.e., the system load, tends to zero, we show that the optimal downlink transmit signal can be obtained in closed-form and comprises a sequence of weighted sums of MRT vectors. Next, based on this result, for general WPCNs with finite system loads, we propose a suboptimal closed-form MRT-based design and a suboptimal semidefinite relaxation (SDR)-based scheme. Our simulation results reveal that the proposed optimal scheme and suboptimal SDR-based design achieve nearly identical performance and outperform two baseline schemes, which are based on linear and sigmoidal EH models. Furthermore, we show that, if the system load of the WPCN is low, the performance gap between the proposed suboptimal solutions is small and becomes negligible as the number of BS antennas tends to infinity.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Downlink; Integrated circuit modeling; MISO communication; Multiple-input multiple-output (MIMO); Non-linear energy harvesting; Radio frequency; Signal design; Signal design; Uplink; Wireless communication; Wireless powered communication

Optimal Resource Allocation and Beamforming for Two-User MISO WPCNs for a Non-linear Circuit-Based EH Model - Shanin, Nikita; Garkisch, Moritz; Hagelauer, Amelie; Schober, Robert; Cottatellucci, Laura (Proceedings of ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2022)
In this paper, we study multi-user multi-antenna wireless power transfer (WPT) systems, where each antenna at the energy harvesting (EH) nodes is connected to a dedicated non-linear rectifier. We propose optimal transmit strategies which maximize a weighted sum of the average harvested powers at the EH nodes subject to a constraint on the power budget of the transmitter. First, for multiple-input single-output (MISO) WPT systems, we prove that the optimal strategy employs maximum ratio transmission (MRT) beamforming and scalar symbols with arbitrary phases and discrete amplitudes following a probability density function (pdf) with at most two mass points. Then, we prove that for single-input multiple-output (SIMO) WPT systems, the optimal transmit symbol amplitudes are discrete random variables, whose pdf also has no more than two mass points. For general multi-user MIMO WPT, we show that the optimal transmit strategy employs scalar unit-norm symbols with arbitrary phases and at most two beamforming vectors. To determine these vectors, we formulate a non-convex optimization problem and obtain an optimal solution based on monotonic optimization. Since the computational complexity of the optimal solution is high, we propose a low-complexity iterative algorithm to obtain a suboptimal solution, which achieves near-optimal performance. Our simulation results reveal that the proposed transmit strategy for multi-user MIMO WPT systems outperforms baseline schemes based on a linear EH model and a single beamforming vector. For a given transmit power budget, we show that the harvested power saturates when increasing the number of transmit antennas. Finally, we observe that the harvested power region spanned by multiple EH nodes is convex and the power harvested at one EH node can be traded for a higher harvested power at the other node

OPTIMAL RESOURCE ALLOCATION AND BEAMFORMING FOR TWO-USER MISO WPCNs FOR A NON-LINEAR CIRCUIT-BASED EH MODEL (Invited Paper) - Shanin, Nikita; Garkisch, Moritz; Hagelauer, Amelie; Schober, Robert; Cottatellucci, Laura (2022 IEEE INTERNATIONAL CONFERENCE ON ACOUSTICS, SPEECH AND SIGNAL PROCESSING (ICASSP), 2022)
CRIS-Team WoS Importer:2023-01-13

Optimal Transmit Signal and Beamforming Design for Integrated Sensing and Power Transfer Systems - Mayer, Kenneth; Lotter, Sebastian; Shanin, Nikita; Brückner, Stefan; Vossiek, Martin; Cottatellucci, Laura; Schober, Robert (IEEE Open Journal of the Communications Society, 2025)
Integrating different functionalities, conventionally implemented as dedicated systems, into a single platform allows utilising the available resources more efficiently. We consider a frame-based integrated sensing and power transfer (ISAPT) system and propose the joint optimisation of the transmit beamforming vectors, the pulse duration, and the subframe durations to combine sensing and wireless power transfer (WPT) functionalities efficiently. In contrast to prior works, we adopt an accurate nonlinear circuit-based energy harvesting (EH) model. We formulate and solve a non-convex optimisation problem for an arbitrary number of EH receivers and sensing targets (STs). The objective is to maximise the weighted sum of the average harvested powers at the EH receivers while ensuring the echo signals reflected by the ST targeted in the corresponding subframe are received with sufficient power for estimating the range to the ST with a prescribed accuracy within the considered coverage region. A method to determine the optimal solution to the problem is derived and two efficient suboptimal schemes are proposed. The performance gap between the upper-bound and the suboptimal schemes is shown to be small. The codesign of the sensing and WPT functionalities and the resulting optimised beampatterns are studied in detail. For high sensing accuracy requirements, the joint transmit signal and beamforming design is found to differ significantly from the optimal transmit signals dedicated to either sensing or WPT. A dedicated transmit signal for WPT is shown to enhance ISAPT system performance when the sensing requirements are less stringen
Keywords: Wireless power transfer; Sensing; Integrated Sensing and Power Transfer; Optimisation

Optimal Transmit Strategy for MIMO WPT Systems with Non-linear Energy Harvesting - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (Proceedings - 17th Annual International Conference on Distributed Computing in Sensor Systems, DCOS 2021, 2021)
In this paper, we study multiple-input multiple-output (MIMO) wireless power transfer (WPT) systems, where the energy harvesting (EH) node is equipped with multiple nonlinear rectennas. We characterize the optimal transmit strategy by the optimal distribution of the transmit symbol vector that maximizes the average harvested power at the EH node subject to a constraint on the power budget of the transmitter. We show that the optimal transmit strategy employs scalar unit-norm input symbols with arbitrary phase and two beamforming vectors, which are determined as solutions of a non-convex optimization problem. To solve this problem, we propose an iterative algorithm based on a two-dimensional grid search, semi-definite relaxation, and successive convex approximation. Our simulation results reveal that the proposed MIMO WPT design significantly outperforms two baseline schemes based on a linear EH model and a single beamforming vector, respectively. Finally, we show that the average harvested power grows linearly with the number of rectennas at the EH node and saturates for a large number of TX antennas.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Energy harvesting; Information Theory; Power Transfer

Optimal Transmit Strategy for Multi-User MIMO WPT Systems With Non-Linear Energy Harvesters - Shanin, Nikita; Schober, Robert; Cottatellucci, Laura (IEEE Transactions on Communications, 2022)
In this paper, we study multi-user multi-antenna wireless power transfer (WPT) systems, where each antenna at the energy harvesting (EH) nodes is connected to a dedicated non-linear rectifier. We propose optimal transmit strategies which maximize a weighted sum of the average harvested powers at the EH nodes subject to a constraint on the power budget of the transmitter. First, for multiple-input single-output (MISO) WPT systems, we prove that the optimal strategy employs maximum ratio transmission (MRT) beamforming and scalar symbols with arbitrary phases and discrete amplitudes following a probability density function (pdf) with at most two mass points. Then, we prove that for single-input multiple-output (SIMO) WPT systems, the optimal transmit symbol amplitudes are discrete random variables, whose pdf also has no more than two mass points. For general multi-user MIMO WPT, we show that the optimal transmit strategy employs scalar unit-norm symbols with arbitrary phases and at most two beamforming vectors. To determine these vectors, we formulate a non-convex optimization problem and obtain an optimal solution based on monotonic optimization. Since the computational complexity of the optimal solution is high, we propose a low-complexity iterative algorithm to obtain a suboptimal solution, which achieves near-optimal performance. Our simulation results reveal that the proposed transmit strategy for multi-user MIMO WPT systems outperforms baseline schemes based on a linear EH model and a single beamforming vector. For a given transmit power budget, we show that the harvested power saturates when increasing the number of transmit antennas. Finally, we observe that the harvested power region spanned by multiple EH nodes is convex and the power harvested at one EH node can be traded for a higher harvested power at the other node

Rate-Power Region of SWIPT Systems Employing Nonlinear Energy Harvester Circuits with Memory - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (IEEE International Conference on Communications, 2020)
In this paper, we study the rate-power region of a simultaneous wireless information and power transfer (SWIPT) system where a transmitter (TX) broadcasts a common signal to an information receiver (IR) and an energy harvester (EH). Since practical EH circuits include a reactive element as part of their signal rectifier and the voltage on this element cannot drop or rise instantaneously, the EH circuit has memory. We model the memory effect of the EH by a Markov reward chain. Furthermore, since an analytical model that includes all nonlinear and memory effects of the EH circuit is not available, we employ a deep neural network (DNN) to model the Markov chain. We formulate an optimization problem to determine the rate-power region of the considered SWIPT system and propose an iterative algorithm based on sequential quadratic programming (SQP) to solve it. Our numerical results show that the optimal input distribution and the rate-power region depend on both the input power level at the EH and the symbol duration.
CRIS-Team Scopus Importer:2020-08-28

Resonant Tunneling Diode- Based THz SWIPT for Microscopic 6G loT Devices - Shanin, Nikita; Clochiatti, Simone; Mayer, Kenneth; Cottatellucci, Laura; Weimann, Nils G.; Schober, Robert (2023 IEEE Globecom Workshops (GC Wkshps), 2023)
In this paper, we study terahertz (THz) simultaneous wireless information and power transfer (SWIPT) for future micro-scale 6G Internet-of- Things (loT) networks. Since Schottky diodes are not efficient for THz energy harvesting (EH), we propose resonant tunneling diodes (RTDs) for EH at the loT receiver (RX). As the electrical properties of RTDs are different from those of Schottky diodes, we develop a novel closed-form EH model for RTD-based RXs. In particular, we model the dependency of the instantaneous RX output power on the instantaneous received power by a non-linear piecewise function, whose parameters are adjusted to fit circuit simulation results. Furthermore, since coherent information detection is challenging at THz frequencies, we employ unipolar amplitude shift keying (ASK) modulation at the transmitter (TX) and utilize the RTD-based EH circuit at the RX to extract both information and energy from the received signal. We formulate an optimization problem to maximize the mutual information between the TX and RX signals subject to constraints on the peak amplitude of the transmitted signal and the required average harvested power at the RX. Moreover, we determine a feasibility condition for the formulated problem and, for high and low required average harvested powers, we derive the achievable information rate numerically and in closed form, respectively. Our simulation results highlight a tradeoff between the information rate and the average harvested power. Finally, we show that this tradeoff is determined by the peak amplitude of the transmitted signal and the maximum instantaneous harvested power for low and high received signal powers, respectively.<br
Keywords: Schottky diodes; Simulation; Circuit simulation; Amplitude shift keying; Resonant tunneling devices; Integrated circuit modeling; Optimization

Wireless Information and Energy Transfer in the Era of 6G Communications - Psomas, Constantinos; Ntougias, Konstantinos; Shanin, Nikita; Xu, Dongfang; Mayer, Kenneth; Tran, Nguyen Minh; Cottatellucci, Laura; Choi, Kae Won; Kim, Dong In; Schober, Robert; Krikidis, Ioannis (Proceedings of the IEEE, 2024)
Wireless information and energy transfer (WIET) represents an emerging paradigm that employs controllable transmission of radio frequency signals for the dual purpose of data communication and wireless charging. As such, WIET is widely regarded as an enabler of envisioned sixth-generation (6G) use cases that rely on energy-sustainable Internet-of-Things (IoT) networks, such as smart cities and smart grids. Meeting the quality-of-service demands of WIET, in terms of both data transfer and power delivery, requires effective codesign of the information and energy signals. In this article, we present the main principles and design aspects of WIET, focusing on its integration in 6G networks. First, we discuss how conventional communication notions, such as resource allocation and waveform design, need to be revisited in the context of WIET. Next, we consider various candidate 6G technologies that can boost WIET efficiency, namely, holographic multiple-input multiple-output, near-field beamforming, terahertz communication, intelligent reflecting surfaces (IRSs), and reconfigurable (fluid) antenna arrays. We introduce respective WIET design methods, analyze the promising performance gains of these WIET systems, and discuss challenges, open issues, and future research directions. Finally, a near-field energy beamforming scheme and a power-based IRS beamforming algorithm are experimentally validated using a wireless energy transfer testbed. The vision of WIET in communication systems has been gaining momentum in recent years, with constant progress with respect to theoretical and also practical aspects. The comprehensive overview of the state of the art of WIET presented in this article highlights the potential of WIET systems and their overall benefits in 6G networks.
CRIS-Team Scopus Importer:2024-05-31
Keywords: 6G mobile communication; Europe; Fluid antennas; holographic multiple-input multiple-output (H-MIMO); intelligent reflecting surface (IRS); Internet of Things; Quality of service; Radio frequency; reconfigurable intelligent surface (RIS); Sustainable development; terahertz (THz); waveform design; Wireless communication; wireless information and energy transfer (WIET)